Carthamus tinctorius L.: a comprehensive review of its ethnomedicine, phytochemistry, pharmacology, and clinical applications - Bai, Haotian; Yang, Jing; Wang, Rui (Frontiers in Pharmacology, 2025)
BackgroundCarthamus tinctorius L. has a long history of ethnomedicinal use for various ailments. This review focuses on the botany, ethnopharmacology, phytochemistry, pharmacological effects, and clinical applications of safflower, aiming to enhance current research in this field.MethodsThe study incorporated relevant scientific literature up to April 2025. It involved the collection of both Chinese and English studies on safflower from various databases, including PubMed, Elsevier, Web of Science, Springer, ScienceDirect, Wiley, ACS, and CNKI (China National Knowledge Infrastructure). Additionally, doctoral and master’s dissertations were included in the analysis.ResultsFrom 1978 to April 2025, various active metabolites were identified, primarily comprising flavonoids, polyacetylenes, and alkaloids, with flavonoids being the predominant group. Extracts and metabolites derived from safflower have demonstrated a range of bioactivities, including antioxidant, hepatoprotective, anti-inflammatory, and anticancer effects. In clinical practice, the effective components of safflower have been utilized in the treatment of cardiovascular and cerebrovascular diseases, diabetes, hepatobiliary conditions, poor blood circulation, sudden deafness, and other ailments.ConclusionThis review elucidates the research surrounding safflower in the domains of ethnopharmacology, phytochemistry, pharmacological activity, and clinical applications. Safflower is known to contain a diverse array of compounds, with flavonoids in particular demonstrating significant pharmacological activity. These compounds are extensively utilized in the pharmaceutical, food, and cosmetic industries, positioning safflower as a promising candidate for development and application in the treatment of various diseases. Nonetheless, research on safflower remains limited, and many active metabolites have yet to be thoroughly investigated in terms of their phytochemical and pharmacological properties. To date, only a handful of active metabolites have been isolated and assessed for their biological activity, and there is a notable deficiency in research regarding their mechanisms of action. Therefore, comprehensive studies are imperative to enhance our understanding of safflower and to substantiate its therapeutic potential.